The Efficiency of AMEn and TMEn Utilization for NE in Broiler Diets - A Yaghobfar (Brazilian Journal of Poultry Science, 2016)
ABSTRACT The experiment was conducted to evaluate the feed intake, body weight gain, total energy (kJ), protein (g) intake, energy and protein efficiency ratio (EER, PER), net energy, and metabolic body weight, on two commercial broiler chickens (Arian and Ross 308 strains). Four treatmentsincluded diets formulated based onAMEn(kJ/g) Total Amino Acid (TAA) (T1), AMEn(kJ/g) Digestible Amino Acid (T2), TMEn (kJ/g) Total Amino Acid (T3), and TMEn (kJ/g) Digestible Amino Acid (DAA) (T4) for commercial broilers chickens. The findings of the study indicated that AMEn or TMEn treatments yielded improved utilization of net energy in 42 days, but did not affect the efficiency of dietary AMEn and TMEn for net energy, diet energy and protein efficiency ratio (EER, PER) in broilers. Findings indicated that NE is a better predictor of poultry feeds than AMEn or TMEn. This is attributed to the fact that AMEn had a significant effect on NE and efficiency of AMEn or TMEn and HI (Heat Increment) for NE value. Finally, NE is the final objective of energy evaluation of feed and feedstuffs for poultry nutrition.